Dielectric properties of nanostructured mixed-oxide films formed by anodizing Al/Zr bilayers - Sepúlveda Sepúlveda, Lina Marcela; Kamnev, Kirill; Mozalev, Alexander (TANGER LTD, 2021)
ZrO2 is a ceramic material suitable for high-temperature coatings, fuel cells as a solid proton-conducting electrolyte, and metal-oxide-semiconductor devices due to its recently explored promising dielectric properties. In this work, anodic nanostructured ZrO2-Al2O3 mixed films were synthesized on substrates via anodizing/reanodizing of a thin Zr layer through a porous anodic alumina (PAA) film at 40/240 V in 0.6 M (COOH)(2) and characterized by scanning electron microscopy and electrochemical impedance spectroscopy (EIS) including the measurements under various bias potentials. The films are composed of ZrO2 nanofingers penetrating the alumina pores, partially mixing with Al2O3. Nanofingers are anchored to a ZrO2 bottom-oxide nanofilm that forms under the PAA during anodization. The EIS reveals a nearly ideal dielectric behavior of the ZrO2-Al2O3 mixed-oxide nanostructured films. After dissolution of the PAA layer, the dielectric properties of the remaining zirconium oxide film become slightly worse, due to the specific structure and deviation from perfect stoichiometry. The ZrO2-Al2O3 mixed-oxide nanostructured film permittivity is calculated to be 11, which is higher than that of alumina (9.8) due to the contribution of ZrO2 nanofingers grown in the alumina nanopores. After the PAA dissolution, the film permittivity increases substantially, up to 46, which is twice the permittivity of ZrO2 (22) grown anodically on zirconium metal in a classical way. The ZrO2-Al2O3 mixed-oxide nanostructured films prepared via the PAA-assisted anodization are of high interest for potential application to various types of capacitors due to their near-ideal dielectric properties. The unique dielectric behavior of the PAA-dissolved ZrO2 film deserves detailed investigation in a future work.

ZrO2 is a ceramic material suitable for high-temperature coatings, fuel cells as a solid proton-conducting electrolyte, and metal-oxide-semiconductor devices due to its recently explored promising dielectric properties. In this work, anodic nanostructured ZrO2-Al2O3 mixed films were synthesized on substrates via anodizing/reanodizing of a thin Zr layer through a porous anodic alumina (PAA) film at 40/240 V in 0.6 M (COOH)(2) and characterized by scanning electron microscopy and electrochemical impedance spectroscopy (EIS) including the measurements under various bias potentials. The films are composed of ZrO2 nanofingers penetrating the alumina pores, partially mixing with Al2O3. Nanofingers are anchored to a ZrO2 bottom-oxide nanofilm that forms under the PAA during anodization. The EIS reveals a nearly ideal dielectric behavior of the ZrO2-Al2O3 mixed-oxide nanostructured films. After dissolution of the PAA layer, the dielectric properties of the remaining zirconium oxide film become slightly worse, due to the specific structure and deviation from perfect stoichiometry. The ZrO2-Al2O3 mixed-oxide nanostructured film permittivity is calculated to be 11, which is higher than that of alumina (9.8) due to the contribution of ZrO2 nanofingers grown in the alumina nanopores. After the PAA dissolution, the film permittivity increases substantially, up to 46, which is twice the permittivity of ZrO2 (22) grown anodically on zirconium metal in a classical way. The ZrO2-Al2O3 mixed-oxide nanostructured films prepared via the PAA-assisted anodization are of high interest for potential application to various types of capacitors due to their near-ideal dielectric properties. The unique dielectric behavior of the PAA-dissolved ZrO2 film deserves detailed investigation in a future work.
Dielectric properties of nanostructured mixed-oxide films formed by anodizing Al/Zr bilayers
Keywords: Anodizing; zirconium oxide; porous anodic alumina; dielectric; Anodizing; zirconium oxide; porous anodic alumina; dielectric